Identifikasi Bahaya dan Pengendalian Risiko Kerja dan Peluang pada Pekerjaan Arsitektur Proyek Konstruksi Gedung XYZ - Valda Yasmina Putri; Putri Ayuni Alayyannur; Denny Ardyanto; Hosiah Hosiah; Savira Aderilla; Revita Dea Sari (Poltekkes Kemenkes Padang, 2024)
Construction projects often face various hazards that can lead to serious or even fatal injuries, especially if risk identification and control are not properly implemented. This study aims to determine the safety risk levels in construction work related to architecture at the XYZ building project. Data collection methods included observation, documentation, and interviews, while the data analysis used the Hazard Identification, Risk Assessment, and Opportunity (IBPRP) method in accordance with Ministerial Regulation PUPR No. 10 of 2021. The research was conducted in August 2024. The risk assessment identified 24 risks in architectural work, with the primary risks including falls from heights, being struck by materials, cuts from tools such as grinders, and electrical shocks. The conclusion of this study is that architectural work in the XYZ building project has 24 identified risks, of which 12 are categorized as very high risk. Control measures such as the use of personal protective equipment (PPE), engineering controls, training, and strict supervision are necessary to reduce risks to an acceptable level. It is recommended to enhance risk control through training and the use of PPE to reduce injuries in construction projects.